Comparative Effects of Copper Sulfate and Zinc Sulfate on Performances of Broiler Chickens (Research in Agriculture Livestock and Fisheries, 2020)
To investigate the effects of copper sulfate (CuSO4.5H2O) and zinc sulfate (ZnSO4) on growth performance, feed intake, feed efficiency and carcass characteristics of commercial broiler an experiment was conducted. Total 80 Cobb-500 of 07 days old chicks were randomly divided into four dietary groups having four replications in each. Four diets were considered: control (T0); CuSO4.5H2O @ 150 mg/kg of commercial diet (T1); ZnSO4 @100 mg/kg on diet (T2); and combination of CuSO4.5H2O + ZnSO4 @ 150 mg/kg + 100 mg/kg of diet (T3), respectively. Initial live weight, live weight gain and feed intake were recorded. Carcass characteristics were observed after slaughtering of birds. The final live weight was significantly (P